The Future of EU Regional Policy - ANDREEA DRĂGOI (Global Economic Observer, 2014)
The regional policy represents the expression of the European Union’s solidarity with less developed countries and regions, aiming at reducing the significant economic, social and territorial disparities that still exist between Europe’s regions. Being an investment policy, EU regional policy supports job creation, competitiveness, economic growth, improved quality of life and sustainable development. During the 2014-2020 period, the EU will invest a total of 351 billion euro in Europe's regions. Our analysis aims at highlighting the possible future development for this common policy, in the new Financial European Framework 2014-2020, underling to what extent, the financial instruments of this policy can contribute to boosting less developed countries and regions, concentrating funds on the areas and sectors where they can make the most difference. Also, this article proposes revealing the convergence of the regional policy objectives with those of the Europe 2020 Strategy.